(Propargylsulfanyl)-2-aza-1, 3, 5-trienes as a direct source for novel family of highly functionalized 4, 5-dihydro-1, 3-thiazoles. Issue 8 (23rd February 2017) - Nedolya, Nina A.; Tarasova, Ol'ga A.; Albanov, Alexander I.; Klyba, Lyudmila V.; Trofimov, Boris A.
Abstract: A novel, simple approach to 2-(1-alkoxyprop-1-enyl)-5-ethenylidene-4, 5-dihydro-1, 3-thiazoles has been disclosed through the reaction of (propargylsulfanyl)-2-aza-1, 3, 5-trienes (readily available from alkoxyallenes, isothiocyanates, and propargyl bromide) with potassium or sodium tert -butoxide (1.1–1.4 equiv) under mild conditions [DMSO/THF (∼1:4–5), ca. −30 °C, 15–30 min]. The process proceeds through deprotonation of an activated SCH2 group, followed by intramolecular [1, 5]-ring-closure. Unlike alkyl-, benzyl-, and allylsulfanyl-analogues, the exclusive or competitive formation of seven-membered azaheterocycles was not observed. Graphical abstract: